(untitled) (Asian-Australasian Journal of Food Safety and Security, 2017)
The study was conducted to determine the total viable count (TVC) and total coliform count (TCC) of unpasteurized, pasteurized and UHT milk samples to assess their microbiological quality. A total of 60 milk samples were collected from different markets of Mymensingh, Gazipur and Sherpur districts. The TVC of milk was performed to determine the bacterial load in supplied milk samples and TCC to determine the coliform bacterial load in collected milk samples. Milk samples were cultured onto various selective media for the isolation of bacteria. The isolated bacteria were identified by cultural properties on different selective media, biochemical tests and finally by PCR. Out of 60 samples 20 unpasteurized milk samples from different markets were found positive for Staphylococcus aureus and 19 unpasteurized milk samples were found positive for Escherichia coli. All the S. aureus were found positive for S. aureus specific 16S rRNA gene by PCR. Out of 19 isolates of E. coli, 15 were found positive for E. coli 16S rRNA gene by PCR. Results of antimicrobial susceptibility test showed that most of the isolates of S. aureus and E .coli were susceptible to azithromycin, streptomycin, gentamicin, norfloxacin, tetracycline and ciprofloxacin but resistant to amoxicillin and erythromycin. The findings of this study revealed the presence of multidrug resistant S. aureus and E. coli in unpasteurized milk samples that posseses a serious threat to public health. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 7-16